Non‐Viral Gene Delivery via Membrane‐Penetrating, Mannose‐Targeting Supramolecular Self‐Assembled Nanocomplexes. (18th February 2013) - Yin, Lichen; Song, Ziyuan; Kim, Kyung Hoon; Zheng, Nan; Gabrielson, Nathan P.; Cheng, Jianjun
<x xml:space="preserve">Abstract</x> Supramolecular self‐assembled nanocomplexes (SSANs) capable of mannose receptor‐mediated endocytosis and permeable to cellular and endosomal membranes are developed via the assembly of multiple rationally designed, function‐specific materials. As a unique non‐viral gene delivery vector, SSANs outperform commercial transfection reagents, including LPF2000, PEI, and jetPEI, by up to 2 orders of magnitude. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>